The Role of Polysomnography for Children with Attention-Deficit/Hyperactivity Disorder - Chien-Heng Lin; Po-Yen Wu; Syuan-Yu Hong; Yu-Tzu Chang; Sheng-Shing Lin; I-Ching Chou (Life)
Objective: Attention-Deficit/Hyperactivity Disorder (ADHD) is a common neurodevelopmental disorder in children, characterized by inattention, hyperactivity, and impulsive behavior. In recent years, studies have shown that patients with ADHD often experience sleep problems, raising clinical interest in the potential role of polysomnography (PSG) in the diagnosis and management of ADHD. This study examines polysomnographic findings in children with ADHD who present with diverse sleep complaints. Methods: A cohort of children aged younger than 18 years, diagnosed with ADHD based on DSM-5 criteria, underwent overnight polysomnography. The study assessed various sleep parameters, including sleep latency, sleep efficiency, total sleep time, and the presence of sleep-disordered breathing. Results: A retrospective analysis was conducted on 36 children (29 boys and 7 girls) aged 6 to 14 years, diagnosed with ADHD, who underwent polysomnography between 2021 and 2024. Polysomnographic findings revealed that 77.78% of the children demonstrated significant snoring. Furthermore, 50.0% were diagnosed with obstructive sleep apnea syndrome (OSAS). In addition, eight children exhibited parasomnias. Among them, six had bruxism, three were diagnosed with periodic limb movement disorder (PLMD), and two experienced sleep talking. Other notable sleep-related conditions included two cases of narcolepsy, one case of prolonged sleep onset latency, and one case of central apnea syndrome. Total sleep time (TST) was significantly longer in females compared to males (400.71 ± 32.68 min vs. 361.24 ± 41.20 min, p = 0.0215), whereas rapid eye movement (REM) latency was longer in males compared to females (118.62 ± 55.60 min vs. 78.57 ± 27.82 min, p = 0.0194). These findings highlight the high prevalence of sleep-disordered breathing (SDB) in children with ADHD who present with sleep disturbances. Furthermore, sleep quality, as indicated by longer TST and shorter REM latency, appears to be better in females with ADHD. Conclusions: The findings of this study underscore the critical role of polysomnography (PSG) in the assessment of children with ADHD. PSG provides an objective evaluation of sleep abnormalities commonly associated with ADHD, which may influence symptom manifestation and treatment outcomes. Notably, the results suggest that females with ADHD exhibit better sleep quality, as indicated by longer total sleep time (TST) and shorter rapid eye movement (REM) latency compared to males. We recommend incorporating polysomnography (PSG) into the comprehensive assessment of children with ADHD who present with significant sleep disturbances. Further research is warranted to investigate the impact of targeted interventions for sleep abnormalities on ADHD symptoms, prognosis, and potential sex-specific differences.